Influence of species and processing techniques on phlorin in Citrus juices as quantified by 1H-NMR spectroscopy. (December 2020) - Jungen, Markus; Schütz, Birk; Schweiggert, Ralf
Abstract: Phlorin (3, 5-dihydroxyphenyl-β-d -glucopyranoside) has been discussed for a long time to be useful for the authentication of Citrus juices as marker for fraudulent processing techniques. In this study, quantitative 1 H-NMR spectroscopy was used to obtain extensive data on phlorin levels in 3866 authentic Citrus juice and juice concentrate samples as well as in 159 peel extracts and whole-processed fruits as obtained from worldwide manufacturers. First, significant species-related differences were found between the phlorin levels in orange, blood orange, lemon, mandarin, as well as red and white grapefruit products. Furthermore, the used juice extraction machinery types were associated with significantly different phlorin intakes. For instance, juices of orange and blood orange made with reamer-type extractors were generally characterized by lower phlorin levels (15 ± 5 and 16 ± 8 mg/L, resp.) than those produced with squeezer-type extractors (21 ± 10 and 38 ± 15 mg/L, resp.). Part of the presented data has been used earlier to support establishing maximum levels of phlorin in the Reference Guidelines of the AIJN Code of Practice for the aforementioned Citrus fruit juices. Graphical abstract: Image 1 Highlights: Phlorin in >4000 citrus juices, concentrates, peel extracts & whole-processed products. Significant differences on species level (orange, lemon, mandarin, and grapefruit). Juices distinguishable from peel extracts & whole-processed products by phlorin. Dejuicing technology appears to influence phlorin intake into the product. Part of the presented data was used to set limits in the AIJN code of practice.